UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN BUDAYA RELIGIUS DI SMPN 44 BANDUNG - Fahrudin, Fahrudin; Firdaus, Endis; Shafiyullah, Alhadi (Universitas Pendidikan Indonesia, 2020)
Abstract. The role of the Islamic Religious Education teacher in learning is very important, especially in instilling students’ religious values. With the application of the religious culture of students in daily life at school, it will have a major influence on the attitudes and practice of students’ religious teachings in their daily life. In general, this study aims to describe the efforts of Islamic Education teachers in improving religious culture at SMPN 44 Bandung. Specifically, the purpose of this study is to describe the planning, implementation, constraints, and outcomes of the religious culture program at SMPN 44 Bandung. This research uses a qualitative approach with descriptive methods. The results of this study indicate that the PAI teacher in improving religious culture at SMPN 44 Bandung can be said to be quite successful, especially in changing the character or behavior of students. Abstrak. Peranan guru Pendidikan Agama Islam dalam pembelajaran sangat penting, khususnya dalam menanamkan nilai-nilai religius siswa. Dengan diterapkannya budaya religius siswa dalam kehidupan sehari-hari di sekolah akan besar pengaruhnya terhadap sikap dan pengamalan ajaran agama siswa dalam kehidupan sehari-hari. Secara umum penelitian ini bertujuan untuk mendeskripsikan upaya guru PAI dalam meningkatkan budaya religius di SMPN 44 Bandung. Secara khusus tujuan penelitian ini adalah untuk mendeskripsikan perencanaan, pelaksanaan, kendala, dan hasil dari program budaya religius di SMPN 44 Bandung. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Hasil dari penelitian ini menunjukkan bahwa guru PAI dalam meningkatkan budaya religius di SMPN 44 Bandung ini bias dikatakan cukup berhasil, khususnya dalam merubah akhlak atau perilaku siswa yang sebelumnya kurang baik menjadi baik. Kata kunci: Upaya Guru PAI, Budaya Religius, PAI di Sekolah